Freedom Of Thought: Legal Protection From Manipulation - Yeremyan, Lilit; Harutyunyan, Davit (Տիգրան Մեծ)
The freedom of thought is stipulated as a fundamental human right in main international human rights instruments at universal and regional levels. Freedom of thought is also guaranteed at the national level in constitutions of many states. It might seem that the legal regulation of freedom of thought is more declarative by its very nature: prima facie, it cannot be limited or violated in practice. Thus, one might as-sume that it does not need any legal protection. In this paper, we argue that the rapid scientific and techno-logical evolution urge the necessity of rethinking the legal content of the freedom of thought and elaborat-ing mechanisms at national and international levels for its effective protection. In particular, we discuss the lawfulness of manipulation as means of influencing the freedom of thought in the age of high technologies and argue that the large-scale intensive manipulation by using special big data processing tools (including artificial intelligence) with the aim to shape the information receivers‘ decision-making process in order to reach a certain outcome motivated by self-interest should be viewed as unlawful interference into the free-dom of thought under International Human Rights Law, consequently creating positive obligations for states.
Keywords: Philosophy